2007
DOI: 10.1128/cvi.00268-06
|View full text |Cite
|
Sign up to set email alerts
|

Optimized FaeG Expression and a Thermolabile Enterotoxin DNA Adjuvant Enhance Priming of an Intestinal Immune Response by an FaeG DNA Vaccine in Pigs

Abstract: One of the problems hindering the development of DNA vaccines is the relatively low immunogenicity often seen in humans and large animals compared to that in mice. In the present study, we tried to enhance the immunogenicity of a pcDNA1/faeG19 DNA vaccine in pigs by optimizing the FaeG expression plasmid and by coadministration of the plasmid vectors encoding the A and B subunits of the Escherichia coli thermolabile enterotoxin (LT). The insertion of a Kozak sequence and optimization of vector (cellular locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 45 publications
4
23
2
Order By: Relevance
“…Some DNA vaccination studies indicate that there was a direct correlation between the level of protein expression in vitro and immunogenicity in mice [34], pigs [30] and chickens [5] [8]. In the present study, although the various HA-expressing DNA construct vaccines did not induce significant antibody responses, there was some enhanced HA antibody responses and some reduction in virus shedding after virus challenge with these vaccines.…”
Section: Discussioncontrasting
confidence: 48%
“…Some DNA vaccination studies indicate that there was a direct correlation between the level of protein expression in vitro and immunogenicity in mice [34], pigs [30] and chickens [5] [8]. In the present study, although the various HA-expressing DNA construct vaccines did not induce significant antibody responses, there was some enhanced HA antibody responses and some reduction in virus shedding after virus challenge with these vaccines.…”
Section: Discussioncontrasting
confidence: 48%
“…Furthermore, addition of plasmid vectors encoding the LTA and LTB subunits to the FaeG DNA vaccine enhanced the IgG response, but did not result in the sIgA response that is desired to completely prevent an F4 + ETEC infection. Nevertheless, a significant reduction was obtained in the amount of F4 + ETEC excreted as well as in the duration of faecal F4 + ETEC excretion (Melkebeek et al, 2007). These data suggest that the systemic DNA immunization is weak in priming mucosal responses.…”
Section: Introductionmentioning
confidence: 84%
“…immunization with pWRGFaeGopt or pWRGFaeGopt in combination with the LT vectors as well as the priming of an F4-specific intestinal mucosal IgG response by i.d. immunization with these vectors followed by an oral F4 boost as seen in a previous study (Melkebeek et al, 2007). Furthermore, we wanted to evaluate if the immunomodulating adjuvant vitD 3 could enhance the mucosal priming by the FaeG DNA vaccine and/or modulate the induced response towards an IgA response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their convenience, stability, and cost, a variety of DNA vaccines encoding the inhibin α (1-32) gene or a fusion with the S gene of the hepatitis B surface antigen have been developed (Han et al, 2008;Wang et al, 2012), and the results showed that an inhibin DNA vaccine was a promising tool for improving animal fertility. However, DNA vaccines face several problems such as low-uptake efficiency (Greenland et al, 2007), dose-dependence (Huang et al, 2008), low immunogenicity in humans and large animals (Melkebeek et al, 2007), and, particularly, antibiotic-resistance-based plasmid selection systems (Galen et al, 2010), making it important to develop an alternative approach for inhibin DNA vaccination.…”
Section: Introductionmentioning
confidence: 99%